Analysing the Relationship between Financial Technology and Commercial Banks' Financial Performance in South Africa - Tshukudu, Darren Kamo; Mokatsanyane, Daniel; Ferreira-Schenk, Sune; Jansen van Rensburg, John George; Sgammini, Ruschelle (Acta Universitatis Danubius. Œconomica, 2022)
During the last decade (2010-2020), the use of financial technology within the banking sector has increased over the world. Therefore, the article aims to determine the relationship between financial technology and commercial banks’ financial performance. A simple linear regression was used along with descriptive analysis and correlation analysis based on the top five banks in South Africa. Two measures of financial performance, return on equity and return on assets, were utilised using secondary bank data for the period of 2011-2021. The findings indicated that within the chosen sample period, there is a relationship between the financial performance of the top five banks in South Africa and the incorporation of financial technology led by the number of mobile subscriptions used for internet banking. Findings also showed that competition within the banking sector is emerging, meaning that South Africa’s banking sector is moving from an oligopolistic environment into a more competitive one. This may be viable for experts within the banking space as it can provide substantial evidence that the transition from traditional-based banking to a more digital approach will be to their benefit in terms of financial performance and gaining market share within the sector.